Analysis of appendicitis management during COVID-19 pandemic: A study of Chinese adult cohorts - Wang, Wei-Di; Lin, Jin-Quan; Zheng, Guang-Wei; Fang, Zhi-Peng; Yan, Yi-Xing (Frontiers in Surgery, 2022)
Background Healthcare seeking behavior has been widely impacted due to the restricted movements of individuals during the Coronavirus disease-19 (COVID-19) pandemic. This study aims to perform risk stratification in patients requiring timely intervention during the recovery periods. Methods Operation notes of acute appendicitis (AA) patients within a hospital were analyzed during three six-month periods (23 January-23 July in 2019, 2020, and 2021, respectively). Patient data were collected retrospectively including demographics, pre-emergency status, perioperative information, postoperative outcomes, and follow-up results. Results 321 patients were included in this study, with 111, 86, and 124 patients in 2019, 2020, and 2021 groups, respectively. The median age of patients decreased by 4 years in 2020 as compared to that in 2019. The proportion of pre-hospitalization symptoms duration of more than 48 hours in the 2020 group was higher (36.05% in 2020 vs. 22.52% in 2019). Length of hospital stay (LOS) in 2020 was shorter than it was during the same period in 2019 (4.77 vs. 5.64) and LOS in 2021 was shorter than in 2019 (4.13 vs. 5.64). Compared to the lockdown period, the proportion of patients with recurrent AA was higher in the post-lockdown period (15.1% vs. 27.4%). The median age was 34 years (vaccinated) vs. 37 years (unvaccinated). Logistic regression suggests that elevated CRP (OR=1.018, CI=1.010-1.028), WBC (OR=1.207, CI=1.079-1.350), female (OR=2.958, CI=1.286-6.802), recurrent (OR=3.865, CI=1.149-12.997), and fecalith (OR=2.308, CI=1.007-5.289) were associated with complicated appendicitis (CA). Conclusion The lockdown measures during the COVID-19 epidemic are shown to be correlated with a reduction in the proportion of AA patients who underwent surgery, particularly in older adults. Risk factors for CA include elevated CRP, WBC, female, recurrent, and fecalith.